Aldosterone Induces the Proliferation of Renal Tubular Epithelial Cells In Vivo but Not In Vitro - Hao, Juan; Liu, Lingjin; Liu, Ziqian; Chen, Gege; Xiong, Yunzhao; Wang, Xiangting; Ma, Xuelian; Xu, Qingyou (Journal of the Renin-Angiotensin-Aldosterone System, 2021)
Objective. To investigate the proliferation effect of aldosterone on renal tubular epithelial cells in vivo and in vitro. Methods. Thirty-two male C57BL/6J mice (20–22 g) were divided randomly into four groups: sham, unilateral nephrectomy (UN), unilateral nephrectomy plus aldosterone infusion (UA), and UA plus eplerenone (UAE). The kidneys were removed 6 weeks after treatment. Expression of proliferating cell nuclear antigen (PCNA) was detected by immunohistochemistry and western blotting. Human kidney proximal tubular epithelial (HK2) and mouse distal convoluted tubule (mDCT) cell lines were stimulated by aldosterone (0, 10−9, 10−8, 10−7, and 10−6 mol/L) in vitro. Cells were collected after 3, 6, 12, 24, 36, and 48 h, and proliferation of each group detected by western blotting, flow cytometry, live imaging, and the MTT assay. In addition, mDCT cells were costimulated with a medium containing a final concentration of 161 mmol/L Na+ and different concentrations of aldosterone, and the number of cells and cellular DNA content was measured by the MTT assay and flow cytometry. Results. Aldosterone could induce a significant increase in the number of PCNA-positive cells in mouse kidneys accompanied by increased deposition of collagen fibers. Eplerenone could inhibit aldosterone-induced cell proliferation and collagen deposition. HK2 cells and mDCT cells administered different concentrations, and different times of aldosterone stimulation failed to cause cell proliferation, and costimulation of aldosterone and salt did not cause proliferation changes in mDCT cells. Conclusions. Aldosterone perfusion can induce proliferation of mouse kidney cells in vivo, and eplerenone can inhibit this change, but aldosterone stimulates HK2 cells and mDCT in vitro without causing their proliferation.